2023
DOI: 10.1097/md.0000000000033821
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the potential relationship between COVID-19 and Behcet’s disease using transcriptome data

Abstract: To investigate the potential role of COVID-19 in relation to Behcet's disease (BD) and to search for relevant biomarkers. We used a bioinformatics approach to download transcriptomic data from peripheral blood mononuclear cells (PBMCs) of COVID-19 patients and PBMCs of BD patients, screened the common differential genes between COVID-19 and BD, performed gene ontology (GO) and pathway analysis, and constructed the protein-protein interaction (PPI) network, screened the hub genes and performed co-expression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In this context, we performed a cohort study using a national dataset that contained epidemiological information about those who were hospitalized due to COVID-19 in Brazil. In brief, our study data found that patients with BD were not at an increased risk of worse COVID-19 outcomes when compared to the general population in Brazil as published before [38,39].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In this context, we performed a cohort study using a national dataset that contained epidemiological information about those who were hospitalized due to COVID-19 in Brazil. In brief, our study data found that patients with BD were not at an increased risk of worse COVID-19 outcomes when compared to the general population in Brazil as published before [38,39].…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, the patients with COVID-19 in the general population presented a case fatality rate of 34.7% which was above the 26.1% observed for patients with BD. However, the case fatality rate for patients with BD was above other populations evaluated in that study, such as patients infected with a) Influenza virus (14.2%), b) another respiratory virus (4.6%), c) another known etiological agent, and d) undefined etiological agent (19.8%) [38]. The same research group published another study conducted with 585,655 hospitalized individuals with a positive result in the SARS-CoV-2 test to evaluate the characterization of demographic data, clinical signs, comorbidities, and outcomes according to the race in Brazil [39].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation